(untitled) (NAU Journal of Technology and Vocational Education, 2025)
The Theory of Planned Behaviours (TPB) has found wide applications due to the importance of the constructs in relation to behaviours. However, construction sustainable behaviours (CSB) have not been given adequate attention in TPB research. This study explores possible construction behaviours in line with the principles of sustainable construction: reducing resource consumption, reusing and recycling resources, protecting nature, eliminating toxics, applying life-cycle costing, and focusing on quality. Based on questionnaire responses, 144 undergraduates in three Departments related to construction education were surveyed for the study. Descriptive statistics, bivariate correlation, hierarchical multiple regression, and structural equation modelling were used for data analysis. Findings reveal important CSB to include choosing recycled and recyclable materials for construction, integrating renewable energy sources over non-renewable ones, designating a particular place for concrete mixing, and insisting on off-site construction over on-site etc. SEM analysis on the association of TBP constructs with actual CSB shows no significant relationship between attitude and behavioural intentions, in favour of others, thus indicating that the constructs of subjective norms, perceived behavioural control and behavioural intentions play pivotal roles in ensuring that undergraduates of construction education uphold pro-environmental behaviours. We discussed the findings, suggesting practical recommendations, and the implications for construction-related studies and curriculum.